Acute Effect of Repeated Sprint Exercise With Blood Flow Restriction During Rest Periods on Muscle Oxygenation - Kojima, Chihiro; Yamaguchi, Keiichi; Ito, Hiroto; Kasai, Nobukazu; Girard, Olivier; Goto, Kazushige (Frontiers in Physiology, 2021)
Purpose: This study aimed to examine the effect of applying BFR during rest periods of repeated cycling sprints on muscle oxygenation. Methods: Seven active males performed 5 × 10-s maximal pedaling efforts with 40-s passive rest, with or without BFR application during rest period. BFR was applied for 30 s between sprints (between 5 and 35 s into rest) through a pneumatic pressure cuff inflated at 140 mmHg. Vastus lateralis muscle oxygenation was monitored using near-infrared spectroscopy. In addition, blood lactate concentration and heart rate were also evaluated. Results: The BFR trial showed significantly lower oxyhemoglobin (oxy-Hb) and tissue saturation (StO2) levels than the CON trial (P < 0.05). However, power output and blood lactate concentration did not significantly differ between the two trials (P > 0.05). Conclusion: Applying BFR during rest periods of repeated cycling sprints decreased muscle oxygenation of active musculature, without interfering with power output during sprints.